Centrinės šiaurės žemaičių tarmės prozodija sociolingvistiniu aspektu - Mažiulienė, Irena Ieva (Baltistica, 1995)
THE PROSODY OF THE CENTRAL NORTHERN ŽEMAITIAN (LOW LITHUANIAN) DIALECT FROM THE STANDPOINT OF SOCIOLINGUISTICSThe general acoustic image of the accent patterns of the dialect shows that the decisive distinctive feature of the acute and circumflex tonemes is a change of phonation which is not infrequently signalled by the variation of pitch (fundamental frequency). Most often, however, the pitch and intensity compensate each other and differentiate the accents in an equal manner.The traditional prosodic features are well preserved in the language of the older generation, while the younger generation already tends to level the distinctive features of the accents. Recessive stress accents are also beginning to wane.The changes in the prosodic patterns are caused by influence of Standard Lithuanian diglossy (also by early diglossy), tendencies in the internal changes of the dialect arisen in the distant past, and by the intermingling of different subdialects.